Cerebral Oximetry Monitoring to Maintain Normal Cerebral Oxygen Saturation during High-risk Cardiac Surgery: A Randomized Controlled Feasibility Trial. (April 2016) - Deschamps, Alain; Hall, Richard; Grocott, Hilary; Mazer, C. David; Choi, Peter T.; Turgeon, Alexis F.; de Medicis, Etienne; Bussières, Jean S.; Hudson, Christopher; Syed, Summer; Seal, Doug; Herd, Stuart; et al.
Abstract : Background: Cerebral oxygen desaturation during cardiac surgery has been associated with adverse perioperative outcomes. Before a large multicenter randomized controlled trial (RCT) on the impact of preventing desaturations on perioperative outcomes, the authors undertook a randomized prospective, parallel-arm, multicenter feasibility RCT to determine whether an intervention algorithm could prevent desaturations. Methods: Eight Canadian sites randomized 201 patients between April 2012 and October 2013. The primary outcome was the success rate of reversing cerebral desaturations below 10% relative to baseline in the intervention group. Anesthesiologists were blinded to the cerebral saturation values in the control group. Intensive care unit personnel were blinded to cerebral saturation values for both groups. Secondary outcomes included the area under the curve of cerebral desaturation load, enrolment rates, and a 30-day follow-up for adverse events. Results: Cerebral desaturations occurred in 71 (70%) of the 102 intervention group patients and 56 (57%) of the 99 control group patients ( P = 0.04). Reversal was successful in 69 (97%) of the intervention group patients. The mean cerebral desaturation load (SD) in the operating room was smaller for intervention group patients compared with control group patients (104 [217] %.min vs. 398 [869] %.min, mean difference, −294; 95% CI, −562 to −26; P = 0.03). This was also true in the intensive care unit ( P = 0.02). There were no differences in adverse events between the groups. Conclusions: Study sites were successful in reversal of desaturation, patient recruitment, randomization, and follow-up in cardiac surgery, supporting the feasibility of conducting a large multicenter RCT. Abstract : Eight Canadian centers randomized 201 patients. Cerebral desaturation (10% relative reduction from baseline) was common and nearly always reversible. Consequently, saturation was far better preserved in patients randomized to intervention than routine care.